Effects of Light Activation, Agent Concentration, and Tooth Thickness on Dental Sensitivity After Bleaching - Moncada, G.; Sepulveda, D.; Elphick, K.; Contente, M.; Estay, J.; Bahamondes, V.; Fernandez, E.; Oliveira, O. B. [UNESP]; Martin, J. (Operative Dentistry Inc, 2013)
Examining three bleaching systems, this in vivo clinical trial evaluated the relationship among tooth sensitivity, light activation, and agent concentration, and it correlated dental sensitivity with tooth thickness.Materials and Methods: Eighty-seven volunteer patients were included. Inclusion criteria were the presence of anterior teeth without restorations as well as the absence of a previous bleaching experience and absence of non-carious cervical lesions or dental pain. Exclusion criteria included pregnancy or breastfeeding, a maximum of TF3 hypoplasia, tetracycline-fluorosis stains, malpositioned teeth, orthodontic treatment, periodontal disease, and/or analgesic/anti-inflammatory intake. Patients were randomly assigned to three bleaching groups: Group A (n=25) was treated with 15% H2O2 and nitrogenous-titanium-dioxide and was light activated (Lase Peroxide Lite, DMC, SaoCarlos, Sao Paulo, Brazil); Group B (n=27) was treated with 35% H2O2 and was light activated (Lase Peroxide Sensy, DMC); and Group C (n=35) was treated with 35% H2O2 (White Gold Office, Dentsply, 38West Clark Ave., Milford, USA) without light activation. Tooth sensitivity (TS) was self-reported by the patients using the visual analog scale (VAS) at baseline (TSO), immediately after treatment (TSI), and at seven days after treatment (TS7). In 46 patients, tooth thickness was determined by computed tomography. TSO, TSI, and TS7 were compared between the A and B groups to determine the effect of concentration and between the B and C groups to determine the effect of light using analysis of covariance. The correlation between tooth thickness and TSI was determined by Spearman Rho test (SPSS 15).Results: Eighty-seven patients were evaluated at baseline, and 61 were evaluated at seven days. Separated by groups, tooth sensitivity, expressed as VAS value at the time points TS0, TS1, and TS7, respectively, were as follows: Group A: 13.76 +/- 13.53, 24.40 +/- 25.24, and 5.94 +/- 5.5; Group B: 15.07 +/- 18.14, 42.4 +/- 31.78, and 8.68 +/- 17.99; and Group C: 10.80 +/- 14.83, 31.51 +/- 29.34, and 7.24 +/- 9.2. Group A showed significantly lower tooth sensitivity than group B at TSI (p=0.032). No differences were observed in the tooth sensitivities between groups B and C. No correlation was encountered between tooth thickness and tooth sensitivity immediately after treatment (Rho=-0.088,p=0.563). The median tooth thickness was 2.78 +/- 0.21 mm.Conclusions: Increases in the concentration of bleaching agents directly affect tooth sensitivity, and LED/laser activation and tooth thickness are not correlated with tooth sensitivity after dental bleaching.